Experiencing William James : Belief in a Pluralistic World - Campbell, James, 1948- (Book collections on Project MUSE., 2017)
William James has long been recognized as a central figure in the American philosophic tradition. Yet while his ideas play a vital, ongoing role in contemporary thinking, there has never been a comprehensive exploration of the thought of this seminal philosopher and psychologist. In Experiencing William James, renowned scholar James Campbell provides the fuller and more complete analysis that James scholarship has long needed. Focusing on James's own ideas rather than his critiques of others, and drawing from a wealth of scholarship that includes the completed editions of his writings and correspondence, Experiencing William James offers an invaluable, comprehensive view of James as he participates in and advances the pragmatic spirit at the core of American philosophy. -- from back cover.